Seeking Risk or Answering Smart? Experimental Evidence on Framing Effects in Elementary Schools - Valentin Wagner (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Losses are painful but how painful are negative outcomes? This paper presents results of a field experiment among 1377 elementary pupils on the effectiveness of loss framing and avoiding negative outcomes on pupils test performance. I compare answers of pupils in a multiple-choice test in math who are endowed with 0 points and earning points is framed as a gain (Control Group) to pupils who are endowed with the maximum number of points but earning points is framed as a loss (Loss Treatment). In a second treatment arm (Negative Treatment) earning points is again framed as a gain but pupils are endowed with a negative amount of points. However, pupils in this treatment could achieve a positive outcome by earning at least half of the points. I find that, on average, the number of correctly solved questions increases significantly in both treatments (Loss and Negative). The multiple-choice testing format allows to identify the underlying channels of improvements. While pupils in the Loss Treatment significantly seem to seek more risk—answer more multiple-choice questions—pupils in the Negative Treatment significantly answer more accurately—increase the share of correctly answered questions. Nevertheless, the Negative Treatment is preferable to the Loss Treatment as both treatments indeed significantly increase performance of high-ability pupils but low-ability pupils significantly perform worse under a loss frame.
Keywords: C93; I20; D80; 330